Lost in translation: The principle of normalisation in prison policy in Norway and the Netherlands. (July 2023) - van de Rijt, Jill; van Ginneken, Esther; Boone, Miranda
The principle of normalisation has gained more prominence in international prison law, with both the United Nations Standard Minimum Rules (UN SMR) and the European Prison Rules (EPR) promoting normalisation to the guiding principles. In general terms, normalisation refers to shaping life in prison in resemblance to life outside prison. However, it largely remains unclear what this principle entails for prison policy. The general formulation in the UN SMR and EPR leave much discretionary room to national prison authorities. By conducting a (comparative) policy analysis, this article aims to uncover the normative standards derived from the UN SMR and EPR and how the principle translates into national laws and policies of Norway and the Netherlands. The analysis shows that although the main provision is generally formulated, some detailed norms are provided in other provisions on how elements of life in prison should be shaped, including limits and restrictions. In Norway and the Netherlands, normalisation is not explicitly mentioned in law, but is (to a varied extent) incorporated in policy. It is shown that, in practice, normalisation is closely tied to reintegration, which has important implications for the principle itself and the norms that are taken as point of reference.